1981
DOI: 10.1095/biolreprod25.3.629
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages in Corpora Lutea of Mice: Characterization and Effects on Steroid Secretion

Abstract: Cells with the ultrastructural

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
66
0
1

Year Published

1994
1994
1998
1998

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(72 citation statements)
references
References 16 publications
5
66
0
1
Order By: Relevance
“…Also, in other organs, macrophages and dendritic cells have been found which are able to regulate the function of endocrine cells, for example, the folliculo-stellate cells in the pituitary [27] and DC-like cells and macrophages in the ovary [28] and the testis [29]. The endocrine regulatory actions of these cells are partly performed in a paracrine way, but also via cell-to-cell contact [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Also, in other organs, macrophages and dendritic cells have been found which are able to regulate the function of endocrine cells, for example, the folliculo-stellate cells in the pituitary [27] and DC-like cells and macrophages in the ovary [28] and the testis [29]. The endocrine regulatory actions of these cells are partly performed in a paracrine way, but also via cell-to-cell contact [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages enhance progesterone production in cultured granulosa cells in rats [18], mice [19] and humans [20]. Our previous study showed that macrophages also promote granulosa cell proliferation in vitro [6].…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have shown that the mature ovary contains many macrophages which may be involved in important endocrine or paracrine processes within the organ (KIRSCH et al, 1981;HALME et al, 1985;BAGAVANDOSS et al, 1988;ADASHI, 1990;MORI, 1990;FUKUMATSU et al, 1992;STERN and COULAM, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the physical contact of macrophages with such steroid-producing cells as luteal and theca cells attracted much attention for the consideration of the paracrine functions of ovarian macrophages (KIRSCH et al, 1981;HALME et al, 1985;BAGA-VANDOSS et al, 1988;ADASHI, 1990;MORI, 1990;FUKUMATSU et al, 1992;STERN and COULAM, 1992). We have clarified the presence of macrophagemacrophage contact through the long cell processes of great numbers pf F4/80-positive cells in the interstitium outside the corpora lutea and follicles.…”
Section: Discussionmentioning
confidence: 99%